Transformations of water governance and social authority in the Hani Rice Terraces - Sun, Jin; Cai, Yin Yin; Hua, Lian Hong; Cheng, Zhi Fen (Frontiers in Environmental Science, 2026)
As global sustainability debates increasingly stress the coupling of social power and ecosystem performance, this study examines the Honghe Hani Rice Terraces as a long-term hydrosocial system. Drawing on historical political ecology, we develop a topographic impact model that links terrain-driven water flows with governance nodes and village institutions across successive regimes—native chieftaincy, people’s communes, and the household responsibility system. Using archival sources, gazetteers, policy documents, and secondary literature, we trace how rules of water allocation, lineage- and village-level cooperation, and ritual/managerial authorities jointly stabilized the terraces’ irrigation network and landscape productivity. While recent restoration policies have improved certain biophysical indicators, the fragmentation of social organizations and uneven access to water and land have heightened vulnerability and management costs in some locales. Our analysis identifies strong institutional continuity in coordination logics encoded in the irrigation infrastructure and terrain, which underpins the terraces’ long-run functioning despite regime shifts. We argue that sustainable governance should avoid a simplistic return to tradition; instead, it should rebuild local subjectivity and institutional resilience, revitalize collaborative mechanisms, clarify multi-level rights and responsibilities, and align contemporary incentives with historically proven coordination rules. Embedding historical experience within modern policy design can better sustain this world-heritage cultural landscape as a coupled human–water system.